SDGs in the Environmental Sciences Program at UniEVANGÉLICA (CIPEEX, 2025)
This paper presents the outline of the 'Research Project' designed to serve as the basis for a Master's Dissertation being developed in the stricto sensu Postgraduate Program in Society, Technology and Environment at the Evangelical University of Goiás (UniEVANGÉLICA). The agenda highlights the importance of studies focused on the level of measurable environmental awareness among magistrates, directors, and secretaries of the district courts comprising the Judiciary in the State of Goiás, concerning both the planning and implementation of the Sustainable Logistics Plan (PSL) for the period 2021–2026. To achieve success, deductive and qualitative approaches were employed, enhanced by bibliographic and documentary techniques, which allowed for the development of descriptive research.
Keywords: UniEVANGÉLICA; PPG STMA; Software; Scientific Papers; SDGs